Adoption and impact of modern varieties of paddy in India: evidence from a nationally representative field survey. Issue 3 (3rd July 2020) - Kumar, Anjani; Tripathi, Gaurav; Joshi, P. K.
Abstract : Purpose: New varieties of paddy are constantly being developed in India in order to sustain yield gains in the face of biotic and abiotic stresses. In this study, the authors attempt to identify the drivers for adoption of new varieties of paddy in India; the authors also estimate the impact on yield of the adoption of new paddy varieties. Design/methodology/approach: Survey data consisted of the reported information from approximately 20, 000 paddy farmers in India. The study employs Cragg's double-hurdle model to study the probability and intensity of adoption of new varieties; we use regression discontinuity design to estimate the change in yield due to adoption of new varieties. Findings: The authors' findings indicate that the adoption of new varieties of paddy in India varies significantly within and between regions; further, the adoption of new varieties is affected by a number of socioeconomic and demographic factors; the authors also find that the adoption of new varieties increases yield significantly. Research limitations/implications: These are observational data and not based on the experiments. The authors relied on farmers' memory to recall the information. Originality/value: The authors suggest the formulation of strategic policies that can cater to the needs of regions and states that are lagging behind in the adoption of new paddy varieties.